Creativity in the Here and Now: A Generic, Micro-Developmental Measure of Creativity - Kupers, Elisa; Van Dijk, Marijn; Lehmann-Wermser, Andreas (Frontiers in Psychology, 2018)
Creativity is a relevant yet elusive concept, and consequently there is a large range of methods to assess creativity in many different contexts. Broadly speaking, we can differentiate between creativity measures on the level of the person (such as the Torrance tests), the level of the creative product (consensual assessment) and the level of the creative process. In the recent literature on children’s creativity, 80% of the studies employed measures on either the person or the product level (AUTHORS , submitted). However, for parents, teachers and employers who wish to stimulate creativity, insight in the (often socially embedded) creative process is badly needed. This move from the inter-individual to the intra-individual level of assessment is furthermore in line with research in many other domains in psychology. Although there is some research focusing more on detailed descriptions of creative processes, the studies are usually purely qualitative and therefore highly context-specific, making generalization difficult. In this paper, we present a newly developed coding frame as a systematic, generic, micro-level measure of creativity. What is unique about this coding frame is that it can be applied to observations of creative processes in many different contexts, and for different kinds of creative tasks. The core of the instrument is that it allows us to assess the two core components of creativity, novelty and appropriateness on an ordinal 4-point scale, at each moment during the creative process. The coding frame can be applied in three steps. The first step is to determine the unit of analysis, that is, the level of detail in which the creative process is assessed. The second step and third steps are coding the units on two ordinal scales of novelty and appropriateness, respectively. In order to illustrate the versatility of our instrument, we apply it to two cases of very different creative processes: a musical composition task (open-ended) and a scientific reasoning task (closed- ended). Last, we demonstrate the possibilities for analyzing this type of dense intra-individual measurements of creativity (time series analysis and state space grids) and discuss the future research that is needed to fully validate the instrument.